PRACTICE OF TABLET DEVICE CLASSESIN KEIO YOCHISHA PRIMARY SCHOOL - ICT EDUCATION FROM PRIMARY SCHOOL FIRST GRADE - Suzuki, Tsugumasa (PEOPLE: International Journal of Social Sciences, 2015)
This research is an ongoing project started in September 2013 at Keio Yochisha Primary School, involving a continuing series of classes taught to a group of thirty-six second grade students, utilizing tablet devices which have been provided for each student in class from the first grade until the present. These students have already been taking classes that use tablet devices for a total of eighteen hours during their first grade. The purpose of this research is not only limited to development of certain skills, such as ICT literacy and twenty-first century skills, but the research also focuses on the introduction of tablet devices as new stationery. Most standard and general tablet functions were selected and tested for the classes. Drawing applications, digital cameras, movie shooting applications and drills have been utilized over the course of the project. Students continue to take classes on how to use tablet devices after moving up to second grade (thirty-one hours total). Results from t assessment of activities in these classes and questionnaires given to students at three points in the first grade suggest improvements in their personal ICT skills. To students, ICT is no longer a set of special gadgets, but has started to become part of their familiar, everyday learning. In this presentation, the process of how such change occurs is described.